An Empirical Study on Commuters Satisfaction Towards Chennai Metro Rail Limited - Kumar.S, shankar; B. Jeyaprabha, Dr. (International Journal of Engineering and Technology, 2018)
Commuterâ€™s are the asset to any transport industry which is to be maintained carefully. All the employee including management must be involved in providing quality services to the commuterâ€™s which leads to commuter satisfaction and retention. Commuterâ€™s is one of the stakeholder of the business. In a competitive scenario commuterâ€™s satisfaction becomes a top priority. The organization should achieve twin objective of customer satisfaction and commuter delight. So it is very much essential for every organization to find the factors which influence commuterâ€™s satisfaction and should continuously monitor and nurture them. The research data is collected through structured questionnaire with a sample size of 60 respondents. It helps to find out the factors related to Chennai Metro Rail Limited services which have a impact on commuterâ€™s satisfactions.Â Â